Operationalizing the Roles of Experiential Learning : Bringing the Partnership to Life - Lewandowski , Adam M.; DePalma , Debbie G.; Englund, Rebecca S.; Cartwright , Melissa M. (Experiential Learning and Teaching in Higher Education, 2022)
This article focuses on the partnership between Discovery Charter School of Rochester, New York, founded in 2011, and Nazareth College Partners for Learning. The Partners for Learning program engages Nazareth College students in partnerships with the children, teachers, and staff of eight urban sites. The authors examine the four critical roles that work to foster program success: (1) Associate Director for the Center for Civic Engagement, (2) Student Site Coordinator, (3) Site Representative, and (4) Classroom Teacher. We describe each of the four roles, how the roles support experiential learning, and, most importantly, how we consistently collaborate to ensure success for all parties. We have gathered multiple forms of reflection, and we share data focusing on the impact of student learning for both personal and professional growth. Finally, Discovery Charter School students describe what having a Partner in their classroom means to them, how the Partners have improved their learning, and how the relationships that have formed over the semester/ year(s) have had an impact on them.